UJI AKTIVITAS ANTIINFLAMASI GEL EKSTRAK BUAH KAKTUS (OPUNTIA ELATIOR MILL.) PADA TIKUS (RATTUS NORVEGICUS L.) YANG DIINDUKSI LAMDA KARAGENAN - Sativa, Oryza; Yuliet, Yuliet; Sulastri, Evi (Univ. Tadulako, 2014)
This research is about anti inflammatory activity of cactus fruits (Opuntia elatior Mill.) extract gel in rats (Rattus norvegicus L.) at induced lamda carragenan in purpose to determine anti inflammatory activity, and concentration of cactus fruits extract in the gel that have an anti inflammatory activity which is equal to sodium diclofenac 1% activity, and to determine the effect of variations in the concentration of cactus fruit extract (Opuntia elatior Mill) on the physical stability of the gel. Extract was made by remaseration method using 70% ethanol. Physical stability test was conducted based on organoleptic, pH, viscosity and homogeneity of the gel. Test on Antiinflammatory activity were divided into 5 groups of treatment. Each rats induced by using lambda carrageenan. The first group of rats was given a gel without active ingredient as a negative control, groups of 2nd, 3rd and 4th rats were given gel cactus fruit extract in concentration of 5%, 10% and 15 % respectively, and 5th groups of rats were given diclofenac sodium gel as a positive control. Diameter and volume of inflammation were measured during 6 hours with 30 minute interval. Colected data were statistically analyzed using ANOVA. The results showed that concentration of cactus fruit extract in proportion of 5%, 10% and 15% in the gel preparation showed different conditions on organoleptic observations and homogeneity even though there was no different in the pH and viscosity during 14 days of storage. The results on anti-inflammatory activity testusing concentration of 5%, 10% and 15% have a recuperation effect on inflammation Gel contining 10% of extract has anti inflammatory activity which equal to 1% of sodium diclofenac activityi.e. the percentage of diameter and volume of inflammation were 63,75% and 20,93%.